PROGRAM OPSI SAHAM DAN PERILAKU PENGAMBILAN RISIKO MANAJEMEN: PENGUJIAN MEDIASI MODERASIAN - ETIK KRESNAWATI; ANANG ALWY SHIHAB; NURUL HIDAYATI (Jurnal Bisnis dan Akuntansi, 2019)
The management stock option program (POSM) is a type of equity compensation that is theoretically predicted to encourage risk alignment between management and principals, which in turn will encourage goal alignment. This study examines this argument on companies that adopted POSM during the period 1999-2016. Utilizing moderated mediation model, we find that management team’s risk taking behavior mediate the effect of POSM on company performance as measured by ROA, but not so when performance is measured by ROE and stock performance index. We also provide evidence that management team considers the company's capital structure, measured by the level of debt, in their risky policy making. Overall, our study documents the critical role of management team’s risk behavior to encourage goal alignment between management and principals.